2010
DOI: 10.1130/g30402.1
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen isotope evidence for semi-aquatic habits among spinosaurid theropods

Abstract: International audienceSpinosaurs were large theropod dinosaurs showing peculiar specializations, including somewhat crocodile-like elongate jaws and conical teeth. Their biology has been much discussed, and a piscivorous diet has been suggested on the basis of,jaw as well as tooth morphology and stomach contents. Although fish eating has been considered plausible, an aquatic or semiaquatic lifestyle has seldom been suggested because of the apparent lack of corresponding adaptations in the postcranial skeleton … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
87
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(96 citation statements)
references
References 38 publications
6
87
0
Order By: Relevance
“…E-mail: Romain.amiot@univ-lyon1.fr. of bones are smaller and less densely intergrown than those of enamel (14), even though several case studies have shown that the original oxygen isotope composition can be preserved in Mesozoic reptile remains (7)(8)(9)(15)(16)(17). Although no method is available to demonstrate definitely whether or not the oxygen isotope composition of fossil vertebrate phosphate was modified by diagenetic processes, several ways to assess the preservation state of the primary isotopic record have been proposed [e.g., (14,(18)(19)(20)(21)].…”
Section: Resultsmentioning
confidence: 99%
“…E-mail: Romain.amiot@univ-lyon1.fr. of bones are smaller and less densely intergrown than those of enamel (14), even though several case studies have shown that the original oxygen isotope composition can be preserved in Mesozoic reptile remains (7)(8)(9)(15)(16)(17). Although no method is available to demonstrate definitely whether or not the oxygen isotope composition of fossil vertebrate phosphate was modified by diagenetic processes, several ways to assess the preservation state of the primary isotopic record have been proposed [e.g., (14,(18)(19)(20)(21)].…”
Section: Resultsmentioning
confidence: 99%
“…Diverse vertebrate faunas are known from calcareous platforms, islands and xeric coastal plains, often inhabited by endemic forms. Although the fossil record from these deposits consists mostly of incomplete specimens, diagnostic elements document unique characters interpreted as a reflection of special adaptations to exceptional combinations of ecological and climatic factors 2,7,[12][13][14] .…”
mentioning
confidence: 99%
“…In wild and captive crocodylians, Amiot et al (2007) O-depleted relative to ocean water by up to 5 ‰, although values greater than 0 ‰ can occur in tropical and subtropical surface waters that experience strong evaporative water loss (reviewed by Gat 1996). These isotopic differences between fresh water and seawater, and the fact that they are recorded in bioapatite, have been used to study habitat use and drinking water sources in aquatic and semi-aquatic fossil vertebrates (Thewissen et al 1996, 2007, Roe et al 1998, Clementz et al 2003, 2006, BillonBruyat et al 2005, Amiot et al 2010). …”
mentioning
confidence: 99%